Deep learning tools for the measurement of animal behavior in neuroscience. (February 2020) - Mathis, Mackenzie Weygandt; Mathis, Alexander
Highlights: Deep neural networks are shattering performance benchmarks in computer vision for various tasks. Using modern deep learning approaches (DNNs) in the lab is a fruitful approach for robust, fast, and efficient measurement of animal behavior. New DNN-based tools allow for customized tracking approaches, which opens new avenues for more flexible and ethologically relevant real-world neuroscience. Abstract : Recent advances in computer vision have made accurate, fast and robust measurement of animal behavior a reality. In the past years powerful tools specifically designed to aid the measurement of behavior have come to fruition. Here we discuss how capturing the postures of animals — pose estimation - has been rapidly advancing with new deep learning methods. While challenges still remain, we envision that the fast-paced development of new deep learning tools will rapidly change the landscape of realizable real-world neuroscience.